STUDI KUALITATIF PEMANFAATAN PLATFORM TIKTOK DALAM PEMBELAJARAN MUSIK TRADISIONAL DAMBUS PADA MATA PELAJARAN SENI BUDAYA DAN PRAKARYA DI SEKOLAH DASAR - Zaki Rakhmawan; Amanda Aulia Rachman; Dodi Pranata; M Iqbal Arrosyad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arts, Culture, and Crafts (SBdP) education in elementary schools plays an important role in instilling an appreciation for the arts and a love for local culture, including traditional music. However, traditional music education, especially the Dambus musical instrument from Bangka Belitung, still tends to be theoretical and uninteresting for students. This study aims to describe the use of the TikTok platform through dambusgoesdigital content in teaching traditional Dambus music in SBdP lessons at SD Negeri 24 Pangkalpinang, as well as to evaluate students' responses to the use of this platform. This study used a descriptive qualitative method with teachers and students as research subjects. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using Miles and Huberman's interactive model, which included data collection, data reduction, data presentation, and conclusion drawing stages. The results showed that the use of the TikTok platform through dambusgoesdigital content was effective as a medium for learning SBdP. The audio-visual content was able to attract students' attention, increase their interest in learning, and facilitate their understanding of the form, sound, and cultural value of the Dambus musical instrument. Students' responses to learning using TikTok showed higher enthusiasm and participation compared to conventional learning. Thus, the TikTok platform can be utilized as an innovative learning medium to support the preservation of traditional regional music in elementary schools, while still requiring the role of teachers in supervising and reinforcing the material.